Improved functional outcomes and cost benefits of door-to-needle time under 30 min in acute ischemic stroke: an observational study - Wang, Jia Dong James; Dong, Ying-Qiu; Yeo, Joshua Y. P.; Teo, Kevin Soon Hwee; Ng, Shiyang; Jing, Mingxue; Chan, Bernard P. L.; Yeo, Leonard L. L.; Chia, Magdalene L. J.; Widjaja, Louis; Wong, Lily Y. H.; Lim, Pamela; et al. (Frontiers in Stroke, 2025)
IntroductionIntravenous thrombolysis (IVT) is cornerstone of acute ischemic stroke(AIS) recanalization therapy. Clinical guidelines advocate achieving Door-to-Needle (DTN) time of 60 min or less, with recent evidence highlighting clinical advantages of even shorter DTN times. However, economic implications of reducing DTN time are less well-studied. This study aims to assess shorter DTN targets impact on clinical outcomes and healthcare costs.MethodsThis observational cohort study included consecutive patients with AIS treated with IVT in a comprehensive stroke center from January 2017 to December 2023. Patients were stratified by DTN time into 4 groups: ≤ 30, 31–45, 46–60, and >60 min. Multivariate linear and logistic regressions were performed to evaluate impact of DTN time on functional and financial outcomes, including modified Rankin's Score (mRS) at 3-months post-AIS, length-of-stay (LoS), total hospitalization cost, symptomatic intracerebral hemorrhage (SICH) and inpatient mortality.Results1,146 patients (62.0% male) with mean age of 68.6 years were included. Overall, 47.6% of patients achieved a mRS of 0–2 at 3 months after AIS. Patients with DTN time of ≤ 30 min demonstrated higher odds of achieving mRS 0–2 at 3 months (OR 2.35, 95% CI 1.26–4.39) compared to DTN time of ≥60 min. They also experienced 4-day shorter length of stay (LoS) until rehabilitation (p = 0.005) and 22.7% reduction in total hospitalization costs (p = 0.004).ConclusionsThis study suggests that DTN time of ≤ 30 min is associated with improved functional outcomes and significant cost benefits, supporting consideration of this more aggressive target for acute stroke units. Further research is needed to assess feasibility and broader impact of implementing a 30-min DTN goal in routine clinical practice.